Governança das políticas ambientais no Brasil: Desafios à construç\~ao de um sistema integrado de avaliaç\~ao - Adriana Maria Magalh\~aes de Moura (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Evaluation is a pillar of results-oriented public management, as necessary input to the decision making process, greater transparency in government actions, control the use of public resources and accountability to society. The evaluation of environmental policies is a relatively new field and it needs to be further investigated, particularly in Brazil, in order to improve the formulation and implementation of these policies. The present study aimed to analyze the systematic evaluation of environmental policies employed by the Federal Government institutions which perform the function evaluation, as well as the area responsible for the formulation of environmental policies. It discusses the extent to which evaluation models adopted meet the needs of managers and propose alternatives for improving the systematic evaluation of environmental policies, through an integrated assessment.
Keywords: Q56; 330; public policy evaluation; monitoring and evaluation systems; environment